Metode Evaluasi Aset Tidak Berwujud dan Modal Intelektual - Putri Nur Asri; Dinda Putri Utami; Dona E Naibaho; Alexander Purba (CV. Ulil Albab Corp, 2022)
In this context, society is entering an era where intangible assets are the company's biggest assets. However, several gaps and uncertainties are presented in the literature for understanding the value of firms based on knowledge-intensive activities. The purpose of this paper is to analyze intangible asset evaluation methods in the context of business, economics and strategic management. This study uses qualitative research. This research is descriptive, bibliographical, inductive in nature. The results of this study are on the existence of intangible asset valuation methods that are intended for certain industries, as public or private, which can be more aligned with the business context; economic or strategic management. It was found that intangible assets are a current topic and are being increasingly discussed in the literature.